2020
DOI: 10.1002/jbmr.4641
|View full text |Cite
|
Sign up to set email alerts
|

Bone Matrix Mineralization and Response to Burosumab in Adult Patients With X-Linked Hypophosphatemia: Results From the Phase 3, Single-Arm International Trial

Abstract: X-linked hypophosphatemia (XLH) is characterized by excess fibroblast growth factor 23 (FGF23) secretion, renal phosphate wasting, and low 1,25(OH) 2 D 3 . Adult patients present with osteomalacia, hypomineralized periosteocytic lesions, bone fragility, and pain. Burosumab is a fully human monoclonal FGF23 antibody approved for XLH treatment. UX023-CL304 was an open-label, phase 3 study investigating the effects of burosumab on osteomalacia in adults with XLH, who remained untreated at least 2 years prior enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Consistent with these findings, the qBEI analysis revealed larger areas of low mineral content (Ca low ) in TIO, supporting previous observations in TIO 35 and other phosphate wasting disorders such as X-linked hypophosphatemia. 36 However, mean mineralization was not changed significantly between TIO and OPO, yet TIO samples exhibited an intermediate state of mineralization when considering control and OPO, pinpointing the HR-pQCT results with only light differences in mineralization. When analyzing Ca low in OPO patients, elevated values became evident in comparison to control subjects.…”
Section: Discussionmentioning
confidence: 68%
“…Consistent with these findings, the qBEI analysis revealed larger areas of low mineral content (Ca low ) in TIO, supporting previous observations in TIO 35 and other phosphate wasting disorders such as X-linked hypophosphatemia. 36 However, mean mineralization was not changed significantly between TIO and OPO, yet TIO samples exhibited an intermediate state of mineralization when considering control and OPO, pinpointing the HR-pQCT results with only light differences in mineralization. When analyzing Ca low in OPO patients, elevated values became evident in comparison to control subjects.…”
Section: Discussionmentioning
confidence: 68%
“…Surprisingly, as mentioned in the results, patients experienced a significant increase in stature during treatment with burosumab, despite being adults and having already completed the growth period. This finding could be attributed to the improvement of deformities in the lower limbs with a better bone mineralization in different compartments (Fratzl‐Zelman et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Burosumab, a human MAB, binds and blocks the action of FGF23. A double-blind, placebo-controlled, phase 3 trial with burosumab on symptomatic adults with XLH showed improvements in the mineralization process of preexisting unmineralized bone matrix ( 52 ). The safety profile of FDA-approved burosumab is claimed to be similar to placebo ( 53 ).…”
Section: Translational Implicationsmentioning
confidence: 99%